On Technological Uses of Local Strain Patterns of the Commercial Zr-Nb Alloys; Advanced Materials Research; Vol. 1040 : High Technology: Research and Applications 2014 (HTRA 2014) - Zuev L. B. Lev Borisovich (Advanced Materials and Nanotechnology, 2014)
Title screen